A revision of the genus Pseudoscopelus Lütken (Chiasmodontidae: Acanthomorphata) with descriptions of three new species - Melo, Marcelo R. S. (Zootaxa, 2010)
Pseudoscopelus Lütken is a genus of meso- and bathypelagic fishes with a worldwide distribution. The genus is the most diversified within the family Chiasmodontidae, containing 16 valid species, three of which are described herein as new: Pseudoscopelus scriptus Lütken, from the western Central and North Atlantic; P. sagamianus Tanaka, from the Eastern Pacific and Indian Ocean; P. altipinnis Parr, widely distributed in the Atlantic and Pacific Oceans; P. cephalus Fowler, only known from the type locality in the Indo-Pacific; P. obtusifrons Fowler, from the Atlantic, Indian and Pacific Oceans; P. scutatus Krefft, widely distributed in the Atlantic, Indian and Pacific Oceans; P. aphos Prokofiev and Kukuev, from the western North Atlantic; P. parini Prokofiev and Kukuev, from the western Central Pacific to Hawaiian islands; P. astronesthidens Prokofiev and Kukuev, from the North Atlantic; P. australis Prokofiev and Kukuev, widely distribution in the southern parts of the Atlantic, Indian, Pacific Oceans, and in the Southern Ocean; P. pierbartus Spitz, Quéro and Vayne, from the North Atlantic and western South Atlantic; P. bothrorrhinos Melo, Walker Jr. and Klepadlo, from the western Pacific and Indian Ocean; P. lavenbergi Melo, Walker Jr. and Klepadlo, from the western North, western Central and western South Atlantic, P. paxtoni new species, from the western South Pacific; P. cordilluminatus new species, from the Indian Ocean and eastern South Atlantic; and P. odontoglossum new species, from the Central Pacific. Herein, Pseudoscopelus stellatus is placed in synonymy of P. scriptus; P. albeolus, in synonymy of P. australis; and P. vityazi, in synonymy of P. parini. Pseudoscopelus microps is confirmed as a junior synonym of P. altipinnis. A key to the species of Pseudoscopelus is provided as well as updated diagnoses, redescriptions, areas and distribution maps, based on extensive examination of collection material and comparison with type specimens.